Dwie wersje dramatu "Brat naszego Boga" Karola Wojtyły - dwa sposoby prezentacji przeżyć wewnętrznych głównego bohatera = Two versions of the drama "Brother of our God" by Karol Wojtyla - two ways of presenting internal experiences of the main character - Bednarczyk-Stefaniak, Emanuela (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The proposed study shows the development of the concept of drama Brother of our God by Karol Wojtyla, from the first version to the second. Both versions of the drama have been considered separately, according to the subject . Descriptive method was applied.
Keywords: Jan Paweł II, papież (1929-2005); dramat polski; 20 w.; John Paul II; polish drama